Studying the dwarf galaxies in nearby groups of galaxies: Spectroscopic and photometric data. Issue 9 (November 2014) - Hopp, U.; Vennik, J.
Abstract Galaxy evolution by interaction‐driven transformation is probably highly efficient in groups of galaxies. Dwarf galaxies with their shallow potential are expected to reflect the interaction most prominently in their observable structure. The major aim of this series of papers is to establish a data base which allows to study the impact of group interaction onto the morphology and star‐forming properties of dwarf galaxies. Firstly, we present our selection rules for target groups and the morphological selection method of target dwarf member candidates. Secondly, the spectroscopic follow‐up observations with the HET are presented. Thirdly, we applied own reduction methods based on adaptive filtering to derive surface photometry of the candidates. The spectroscopic follow‐up indicate a dwarf identification success rate of roughly 55 %, and a group member success rate of about 33 %. A total of 17 new low surface‐brightness members is presented. For all candidates, total magnitudes, colours, and light distribution parameters are derived and discussed in the context of scaling relations. We point out short comings of the SDSS standard pipeline for surface photometry for these dim objects. We conclude that our selection strategy is rather efficient to obtain a sample of dim, low surface brightness members of groups of galaxies within the Virgo super‐cluster. The photometric scaling relation in these X‐ray dim, rather isolated groups does not significantly differ from those of the galaxies within the local volume. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)